Predictors of smoking cessation during pregnancy: a systematic review and meta-analysis - Riaz, Muhammad; Lewis, Sarah; Naughton, Felix; Ussher, Michael (Wiley, 2018)
AIM: To identify factors found in the research literature to be associated with smoking cessation in pregnancy.